Intellectual Property Protection in Startup-Freelancer Relationships: An Analysis of the Legal Vacuum in Copyright and Trade Secrets - Vizta Dana Iswara; Elza Syarief; Lu Sudirman (Journal of Law and Policy Transformation, 2024)
Startups play an important role in the digital economy by bringing innovation and growth. Intellectual property can be in the form of copyrights, patents, trade secrets and trademarks owned by a startup business. However, the protection of intellectual property, especially copyrights and trade secrets, still faces major challenges. This article examines the legal lacuna in intellectual property protection, particularly regarding the relationship between startups and freelancers who often contribute valuable ideas and works. Using Philipus M. Hadjon's theory of legal protection and Gustav Radbruch's theory of legal certainty, this article highlights the need for stricter regulation to address the legal vacuum. Reforms are needed to improve trade secret protection and ensure better legal certainty. The conclusion suggests that strengthening intellectual property regulations will support the sustainability and competitiveness of startups, as well as protect their innovative assets in a competitive digital environment.